When friendship matters: The role of peer relationship quality in predicting loneliness among generation Z - Kayla Kinanti Rahani; Rizky Putra Santosa (Universitas Trunojoyo Madura, 2026)
The present study examined the role of peer relationship quality in predicting loneliness among Generation Z. A quantitative approach with a cross-sectional design was employed. A total of 155 individuals aged 16–22 years in Indonesia were recruited using purposive sampling. Data were collected through an online survey using the Friendship Quality Scale (FQS) to assess peer relationship quality and the UCLA Loneliness Scale Version 3 to measure loneliness. The results indicated that peer relationship quality significantly predicted loneliness among Generation Z, demonstrating a negative association (β= −0.695, p .001). Furthermore, peer relationship quality accounted for 61.1% of the variance in loneliness (R² = .611, f² = 1.57). These findings suggest that individuals who perceive their peer relationships as higher in quality tend to experience lower levels of loneliness. The importance of developing psychosocial interventions aimed at improving peer relationship quality is emphasized by the findings from a practical perspective. Future research is required to examine other contributing factors such as family support and mental health conditions to further understand loneliness among Generation Z.